Analysis of the Accounting Information System of Merchandise Inventory at PT. Bintang Toba Lestari - Nasution, Jeki; Siswanto, Siswanto; Fransiscus, Raymond (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: Companies must ensure accurate merchandise inventory management through effective accounting information systems and robust internal control procedures. However, PT Bintang Toba Lestari continues to experience inaccuracies due to non-compliance with standard operating procedures (SOPs), inadequate documentation practices, and excessive reliance on staff supervision, which can compromise operational efficiency and data integrity. This study aims to analyze the merchandise inventory accounting information system and evaluate the effectiveness of internal control mechanisms implemented at PT Bintang Toba Lestari. Materials and methods: This research employed a qualitative descriptive approach. Primary data were collected through structured interviews with the HRD department and several staff members involved in merchandise inventory activities. Additional insights were obtained through direct field observations and the examination of secondary data sourced from company documentation. Data analysis procedures included data reduction, data presentation, and conclusion drawing. Results: Findings reveal that the company’s inventory recording and reporting procedures generally function effectively and align with the principles of accounting information systems. However, weaknesses were identified within the internal control structure, particularly the overlap of duties in the warehouse division, which increases the risk of errors and reduces control reliability. Furthermore, documentation practices and adherence to SOPs remain inconsistent during inventory implementation. Conclusions: While the merchandise inventory accounting information system at PT Bintang Toba Lestari is operational and largely appropriate, the internal control system requires improvement. Strengthening functional segregation, enhancing documentation procedures, and ensuring compliance with established SOPs are essential to improving inventory accuracy and internal control effectiveness.